O PLANEJAMENTO ESTRATÉGICO NOS MUNICIPIOS DO COREDE NOROESTE COLONIAL - Siedenberg, Dieter R.; Ri, Marele K. D.; Souza, Jose D. d.; Griebeler, Marcos P. D.; Pasqualini, Fernanda; Gutknecht, Raquel; Bernardi, Tamiris; Santos, Tamires d. S. d.; Bonfada, Daiane; Monteciello, Cristian (Salão do Conhecimento, 2013)
Resumo